Evaluation of Academic Competencies Through Standardized Instruments - Gema Santiago Gómez; Sara Redondo Duarte; Oscar Garcia López (Laureate Education Inc, 2018)
The aim of this investigation is to assess the correlation among different competencies-assessment systems available on the market to measure social skills in the university environment. In order to carry out the research, three self-perception competency tests were used, and 30 competencies were evaluated in a Likert scale with several response levels: the LPA-Q, the ESCI-U, and the CompeUEM. The three questionnaires were completed by 57 university students. The results show a low degree of agreement among the different questionnaires in relation to measuring the same competencies, as well as an unclear factor structure.